Major royal jelly proteins accelerate onset of puberty and promote ovarian follicular development in immature female mice - Xin Liu; Chenmin Jiang; Yong Chen; Fangxiong Shi; Chaoqiang Lai; Lirong Shen (Food Science and Human Wellness)
The major royal jelly proteins (MRJPs) are the central constituents responsible for the specific activities of royal jelly. Here MRJPs via oral administration daily for 45 consecutive days were evaluated the effects on the reproductive parameters in immature female mice (FM). Neonatal FM were divided into four groups fed MRJPs with doses of 0, 125, 250 and 500 mg/kg/body weight (M125, M250 and M500). The results in M125, M250 and M500 showed that the times of estrus were accelerated by 10.7%, 15.5% and 10.7%, the secondary follicles number were increased by 50.7%, 78.8% and 38.6%, the Graafian follicles were increased by 600.0% and 774.0% and 150.0%, respectively. M500 induced multi-oocyte follicles. The serum estradiol levels of the three groups were increased by 47.1%, 64.9% and 31.1%, the action of MRJPs raising hormone secretion level is mainly via upregulating expression of ERβ gene. Antioxidant parameters of ovarian tissue showed that the malondialdehyde levels in M125 and M250 were decreased, the superoxide dismutase activities and glutathione peroxidase activities in M125 and M250 were increased. In conclusion, MRJPs may accelerate onset of puberty and promote follicular development in FM. Our findings would facilitate better understanding of the benefit effect of MRJPs as the key ingredient in royal jelly on promoting fertility performance.